2003
DOI: 10.2337/diacare.26.10.2754
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Is a Risk Factor for the Development of Type 2 Diabetes in Japanese Americans

Abstract: OBJECTIVE -Increasing evidence from a cohort of Caucasians recently suggests that an elevated level of C-reactive protein (CRP) is associated with an increased risk of developing type 2 diabetes. However, Japanese subjects are skewed to lower CRP concentrations than westerners. Therefore, the effect of CRP on the development of type 2 diabetes among Japanese is unclear.RESEARCH DESIGN AND METHODS -We examined 396 male and 551 female nondiabetic Japanese Americans who underwent a 75-g oral glucose tolerance tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 30 publications
8
105
3
2
Order By: Relevance
“…A study in Mexico City showed that the association was strong and significant in women but not in men [17]. An independent association was observed in women aged 45-year or older in the United States [7], in middle-aged men in Eastern Finland [10] and in Japanese American men and women [9]. In a matched case-control study in a high risk population of Pima Indians, no association between CRP and diabetes was found [20], possibly due to the lack of power due to the small sample size.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A study in Mexico City showed that the association was strong and significant in women but not in men [17]. An independent association was observed in women aged 45-year or older in the United States [7], in middle-aged men in Eastern Finland [10] and in Japanese American men and women [9]. In a matched case-control study in a high risk population of Pima Indians, no association between CRP and diabetes was found [20], possibly due to the lack of power due to the small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…The association between inflammatory markers and incident diabetes has been examined in a few prospective studies in other populations [7], [8], [9], [10], [17], [18] and [19]. A study in Mexico City showed that the association was strong and significant in women but not in men [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is heterogeneity between studies, with some demonstrating an independently positive association of CRP with incident diabetes [3][4][5][6][7][8][9][10][11], while others show no association after adjustment for adiposity and insulin resistance [12][13][14][15]. Differences in the association between CRP and diabetes by sex have also been reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%